Lectin Pathway of Complement Activation Is Associated with Vulnerability of Atherosclerotic Plaques - Fumagalli, Stefano; Perego, Carlo; Zangari, Rosalia; De Blasio, Daiana; Oggioni, Marco; De Nigris, Francesca; Snider, Francesco; Garred, Peter; Ferrante, Angela M. R.; De Simoni, Maria-Grazia (Frontiers in Immunology, 2017)
Inflammatory mechanisms may be involved in atherosclerotic plaque rupture. By using a novel histology-based method to quantify plaque instability here we assess whether the activation of the lectin complement pathway (LP), a major inflammation arm, could represent an index of plaque instability. Plaques from 42 consecutive patients undergoing carotid endarterectomy were stained with hematoxylin-eosin and the lipid core, cholesterol clefts, hemorrhagic content, thickness of tunica media and intima, including or not infiltration of cellular debris and cholesterol, were determined. The presence of ficolin-1, -2 and -3 and mannose-binding lectin (MBL), LP initiators, was assessed in the plaques by immunofluorescence and in plasma by ELISA. LP activation was assessed in plasma by functional in vitro assays. Patients presenting low stenosis (≤75%) had higher hemorrhagic content than those with high stenosis (>75%), indicating increased erosion. Increased hemorrhagic content and tunica media thickness, as well as decreased lipid core and infiltrated content were associated with vulnerable plaques and therefore used to establish a plaque vulnerability score that allowed to classify patients according to plaque vulnerability. Ficolins and MBL were found both in plaques’ necrotic core and tunica media. Patients with vulnerable plaques showed decreased plasma levels and intraplaque deposition of ficolin-2. Symptomatic patients experiencing a transient ischemic attack had lower plasma levels of ficolin-1. We show that the LP initiators are present within the plaques and their circulating levels change in atherosclerotic patients. In particular we show that decreased ficolin-2 levels are associated with rupture-prone vulnerable plaques, indicating its potential use as marker for cardiovascular risk assessment in atherosclerotic patients.